GM1 Ganglioside Promotes Osteogenic Differentiation of Human Tendon Stem Cells - Sonia Bergante; Pasquale Creo; Marco Piccoli; Andrea Ghiroldi; Alessandra Menon; Federica Cirillo; Paola Rota; Michelle M. Monasky; Giuseppe Ciconte; Carlo Pappone; Pietro Randelli; Luigi Anastasia (Stem Cells International)
Gangliosides, the sialic acid-conjugated glycosphingolipids present in the lipid rafts, have been recognized as important regulators of cell proliferation, migration, and apoptosis. Due to their peculiar localization in the cell membrane, they modulate the activity of several key cell receptors, and increasing evidence supports their involvement also in stem cell differentiation. In this context, herein we report the role played by the ganglioside GM1 in the osteogenic differentiation of human tendon stem cells (hTSCs). In particular, we found an increase of GM1 levels during osteogenesis that is instrumental for driving the process. In fact, supplementation of the ganglioside in the medium significantly increased the osteogenic differentiation capability of hTSCs. Mechanistically, we found that GM1 supplementation caused a reduction in the phosphorylation of the platelet-derived growth factor receptor-β (PDGFR-β), which is a known inhibitor of osteogenic commitment. These results were further corroborated by the observation that GM1 supplementation was able to revert the inhibitory effects on osteogenesis when the process was inhibited with exogenous PDGF.